KARAKTERISTIK KELUARGA, KESIAPAN MENIKAH ISTRI, DAN PERKEMBANGAN ANAK USIA 3-5 TAHUN - Tsania, Nurlita; Sunarti, Euis; Krisnatuti, Diah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
Marital readiness was considered as an important indicator for successful marriage and also could enhance child development, espeially for early phase of family and early childhood. However, the study about marital readiness and child development were still limited. The study was a retrospective and cross sectional design of 120 families whose children aged 3-5 years old. Samples were selected by stratified nonproportional simple random sampling in two areas in Ratu Jaya and Bojong Pondok Terong, Cipayung Sub district, Depok. Theresults showed that attainment of wife’s marital readiness was in middle category which was below 65; it means that the family did not have good marital readiness. Two of marital readiness dimension were intellectual and financial readiness which was still below 50 or in low category. Maternal length of education was correlated positively significant with marital readiness, while marital readiness was correlated positively significant with child development. The results of regression showed the child development was influenced positively by sex of children, age of children, and marital readiness (intellectual and individual readiness). Meanwhile, the child development was influenced negatively by length of marriage.